The Addition Effects of Souropus androgynus Powder in the Basic Local Feed to Broiler Performance - Mide, Muhammad Zain; Harfiah, . (Buletin Nutrisi dan Makanan Ternak, 2013)
This research aim is to study the addition effect of leaf powder of Sauropus androgynus in the feed ration local basis to broiler performance. Sixty four broilers, day old chick (doc), were randomly assigned in 16 experimental cages (4 broilers/cage) with the size of 100 cm x 50 cm x 60 cm/cage. The experiment was conducted according to the Complete Randomized Design, consisted of 4 treatments and 4 replications. The treatment was: T0 = basic ration (control), T1 = basic ration + 1%  of Suropus androgynus, T2 = basic ration  + 2% of Suropus androgynus and T3 = basic ration + 3  % Sauropus androgynus. The statistical analysis indicated that the addition effect of Sauropus androgynus leaf powder in the feed ration local basis is not significant (P>0,05) on  the ration consumption, protein consumption and conversion ration to broiler. However, it effects (P<005) to the weight increase and protein efficiency ratio of broiler. Duncan Test indicated that the weight increase of P1, P2, and P3 has an effect (P<0,05) higher than P0. and also for P2 the effect is higher than P1 and P3, but P1 and P3 are not significantly different (P>005). Conclution: 1). The powder addition of Sauropus androgynus in the ration has the same effect on ration consumption, protein consumption, and ration convertion to broiler. 2). The biological data shows that all treatments of powder addition of Sauropus androgynus leaf have an effect in increasing the weight and protein efficiency ratio higher than control.